2022
DOI: 10.1158/0008-5472.can-22-1190
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Spatial Profiling of Immune Populations in Pancreatic Ductal Adenocarcinoma Reveals Tumor Microenvironment Heterogeneity and Prognostic Biomarkers

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive disease with poor 5-year survival rates, necessitating identification of novel therapeutic targets. Elucidating the biology of the tumor immune microenvironment (TiME) can provide vital insights into mechanisms of tumor progression. In this study, we developed a quantitative image processing platform to analyze sequential multiplexed IHC data from archival PDAC tissue resection specimens. A 27-plex marker panel was employed to simultaneously phenot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
(51 reference statements)
0
18
1
Order By: Relevance
“…While interindividual variability and intraindividual heterogeneity in terms of tumortumor heterogeneity are accounted for in this study, our QSP model ignores intratumoral heterogeneity and assumes that tumors are well-mixed. Spatial immune architecture such as the proximity of certain cell types has been shown to be associated with disease prognosis (63). Agent-based models have been developed and integrated with QSP models to explore the effects of intratumoral heterogeneity on treatment responses (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…While interindividual variability and intraindividual heterogeneity in terms of tumortumor heterogeneity are accounted for in this study, our QSP model ignores intratumoral heterogeneity and assumes that tumors are well-mixed. Spatial immune architecture such as the proximity of certain cell types has been shown to be associated with disease prognosis (63). Agent-based models have been developed and integrated with QSP models to explore the effects of intratumoral heterogeneity on treatment responses (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma tissue is surrounded by massive immune cell infiltration, resulting in the creation of a complex immune microenvironment that allows osteosarcoma cells to grow within the bone by creating an immunosuppressive microenvironment to maintain their survival and proliferation. [35][36][37] A robust immunosuppressive microenvironment is positively correlated with overactivation of molecules associated with immune suppression, such as indoleamine 2,3-dioxygenase (IDO), programmed cell death protein 1 (PD-1), interleukin-10 (IL-10), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), and signal transducer and activator of transcription 3 (STAT3), due to their immunosuppressive effects mediated by myeloid-derived suppressor cells (MDSCs), TAMs, and regulatory T lymphocytes (Tregs) [38][39][40][41][42][43] (Fig. 2).…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%
“…Tissue structures such as tertiary lymphoid structures, identified with multiplex imaging, are predictive biomarkers of immunotherapy response in melanoma 11,12 . Recently, spatial biomarkers involving multiple cell types have been identified that predict response to immune checkpoint inhibitors in cutaneous T cell lymphoma 13 and patient survival pancreatic ductal adenocarcinoma 14 . Employment of multiplex imaging methods in breast cancer has revealed that single-cell spatial context has prognostic relevance and shows correlations with transcriptomic and genomic features of tumors [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%